Formação humana e cuidado de si: um encontro explosivo ou a possibilidade de pensar de outro modo a racionalidade e a ética na educação? - Pagni, Pedro Ângelo [UNESP] (My University, 2011)
This essay discusses the issue of the contemporary fall of human shaping as an opening possibility to think it in another way. For that purpose it analyzes the latest favorite courses at the Collège de France by Michel Foucault in order to verify the notion possibility of care of oneself and of psychology to regard the human shaping with a different look. By approaching the point of view of the esthetics of existence, it offers reasons with the possibility of life concept as a work of art to be an alternative to the fall of the modern concept of shaping in the contemporary times.

O presente ensaio discute o problema da queda contemporânea da formação humana como uma possibilidade de abertura para pensá-la de outro modo. Para tal propósito, analisa os últimos cursos proferidos no Collège de France por Michel Foucault para averiguar a possibilidade da noção de cuidado de si e de psicagogia lançarem outro olhar sobre a formação humana. Ao adotar o ponto de vista da estética da existência argumenta pela possibilidade da concepção da vida como obra de arte ser uma alternativa à queda do moderno conceito de formação na contemporaneidade.
Humane shaping and care of oneself: an explosive meeting or the possibility to think rationally and ethics in education in another way?
Keywords: formação cultural; cuidado de si; arte de viver; Foucault